Difference between revisions of "2011 AIME I Problems/Problem 15"
(→Solution 2) |
|||
Line 66: | Line 66: | ||
− | Starting off like the previous solution, we know that a + b + c = 0, and ab + bc + ac = -2011 | + | Starting off like the previous solution, we know that a + b + c = 0, and ab + bc + ac = -2011. |
− | Therefore, <math>c = -b-a</math> | + | Therefore, <math>c = -b-a</math>. |
− | Substituting, <math>ab + b(-b-a) + a(-b-a) = ab-b^2-ab-ab-a^2 = -2011</math> | + | Substituting, <math>ab + b(-b-a) + a(-b-a) = ab-b^2-ab-ab-a^2 = -2011</math>. |
− | Factoring the perfect square, we get: <math>ab-(b+a)^2=-2011</math> or <math>(b+a)^2-ab=2011</math> | + | Factoring the perfect square, we get: <math>ab-(b+a)^2=-2011</math> or <math>(b+a)^2-ab=2011</math>. |
− | Therefore, a sum (<math>a+b</math>) squared minus a product (<math>ab</math>) gives <math>2011</math>. | + | Therefore, a sum (<math>a+b</math>) squared minus a product (<math>ab</math>) gives <math>2011</math>.. |
<br/> | <br/> | ||
Line 80: | Line 80: | ||
We can guess and check different <math>a+b</math>’s starting with <math>45</math> since <math>44^2 < 2011</math>. | We can guess and check different <math>a+b</math>’s starting with <math>45</math> since <math>44^2 < 2011</math>. | ||
− | <math>45^2 = 2025</math> therefore <math>ab = 2025-2011 = 14</math> | + | <math>45^2 = 2025</math> therefore <math>ab = 2025-2011 = 14</math>. |
Since no factors of <math>14</math> can sum to <math>45</math> (<math>1+14</math> being the largest sum), a + b cannot equal <math>45</math>. | Since no factors of <math>14</math> can sum to <math>45</math> (<math>1+14</math> being the largest sum), a + b cannot equal <math>45</math>. | ||
− | <math>46^2 = 2116</math> making <math>ab = 105 = 3 * 5 * 7</math> | + | <math>46^2 = 2116</math> making <math>ab = 105 = 3 * 5 * 7</math>. |
− | <math>5 * 7 + 3 < 46</math> and <math>3 * 5 * 7 > 46</math> so <math>46</math> cannot work either | + | <math>5 * 7 + 3 < 46</math> and <math>3 * 5 * 7 > 46</math> so <math>46</math> cannot work either. |
<br/> | <br/> | ||
− | We can continue to do this until we reach <math>49</math> | + | We can continue to do this until we reach <math>49</math>. |
− | <math>49^2 = 2401</math> making <math>ab = 390 = 2 * 3 * 5* 13</math> | + | <math>49^2 = 2401</math> making <math>ab = 390 = 2 * 3 * 5* 13</math>. |
<math>3 * 13 + 2* 5 = 49</math>, so one root is <math>10</math> and another is <math>39</math>. The roots sum to zero, so the last root must be <math>-49</math>. | <math>3 * 13 + 2* 5 = 49</math>, so one root is <math>10</math> and another is <math>39</math>. The roots sum to zero, so the last root must be <math>-49</math>. | ||
Line 98: | Line 98: | ||
<br/> | <br/> | ||
− | <math>|-49|+10+39 = 98 | + | <math>|-49|+10+39 = \boxed{098}</math> |
− | |||
− | |||
== See also == | == See also == |
Revision as of 17:30, 23 June 2014
Contents
Problem
For some integer , the polynomial
has the three integer roots
,
, and
. Find
.
Solution
With Vieta's formula, we know that , and
.
since any one being zero will make the the other 2
.
. WLOG, let
.
Then if , then
and if
,
.
We know that ,
have the same sign. So
. (
and
)
Also, maximize when
if we fixed
. Hence,
.
So .
so
.
Now we have limited a to .
Let's us analyze .
Here is a table:
![]() | ![]() |
---|---|
![]() | ![]() |
![]() | ![]() |
![]() | ![]() |
![]() | ![]() |
![]() | ![]() |
We can tell we don't need to bother with ,
, So
won't work.
,
is not divisible by
,
, which is too small to get
,
is not divisible by
or
or
, we can clearly tell that
is too much
Hence, ,
.
,
.
Answer:
Solution 2
Starting off like the previous solution, we know that a + b + c = 0, and ab + bc + ac = -2011.
Therefore, .
Substituting, .
Factoring the perfect square, we get: or
.
Therefore, a sum () squared minus a product (
) gives
..
We can guess and check different ’s starting with
since
.
therefore
.
Since no factors of can sum to
(
being the largest sum), a + b cannot equal
.
making
.
and
so
cannot work either.
We can continue to do this until we reach .
making
.
, so one root is
and another is
. The roots sum to zero, so the last root must be
.
See also
2011 AIME I (Problems • Answer Key • Resources) | ||
Preceded by Problem 14 |
Followed by - | |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 | ||
All AIME Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.